Epidemiology and clinical features of Skin and Soft Tissue Infections Caused by PVL-Positive and PVL-Negative Methicillin-Resistant Staphylococcus aureus Isolates in inpatients in China: a single-center retrospective 7-year study - Ye Jin; Wangxiao Zhou; Qi Ge; Ping Shen; Yonghong Xiao (Emerging Microbes and Infections, 2024)
Previous studies have mainly focused on outpatient cases of skin and soft tissue infections (SSTIs), with limited attention to inpatient occurrences. Thus, we aimed to compare the clinical parameters of inpatients with SSTIs, performed genomic characterization, and determined the subtypes of Panton-Valentine leucocidin (PVL) bacteriophages of methicillin-resistant Staphylococcus aureus (MRSA) strains isolated from these patients. We found that PVL-positive patients had shorter hospital stays (mean, 9 vs. 24 days; p < 0.001) and abscess resolution durations (mean, 8 vs. 13 days; p < 0.01). PVL-positive MRSA-induced SSTIs were more frequently associated with abscesses [36/55 (65.5%) vs. 15/124 (12.1%), p < 0.001], with 52.7% undergoing incision and drainage; over 80% of PVL-negative patients received incision, drainage, and antibiotics. In PVL-positive patients receiving empirical antibiotics, anti-staphylococcal agents such as vancomycin and linezolid were administered less frequently (32.7%, 18/55) than in PVL-negative patients (74.2%, 92/124), indicating that patients with PVL-positive SSTIs are more likely to require surgical drainage rather than antimicrobial treatment. We also found that the ST59 lineage was predominant, regardless of PVL status (41.3%, 74/179). Additionally, we investigated the linear structure of the lukSF-PV gene, revealing that major clusters were associated with specific STs, suggesting independent acquisition of PVL by different strain types and indicating that significant diversity was observed even within PVL-positive strains detected in the same facility. Overall, our study provides comprehensive insights into the clinical, genetic, and phage-related aspects of MRSA-induced SSTIs in hospitalized patients and contributes to a more profound understanding of the epidemiology and evolution of these pathogens in the Chinese population.